Improving the power quality of the wind power system using low cost topology. (3rd April 2017) - Vani, E.; Rengarajan, N.
Abstract: In this paper, Vienna rectifier (three-phase/three-switch converter) and Z-source inverter (ZSI) have been proposed with fewer number switches to enhance the power quality of off-grid wind power system (WPS). Conventional WPS used three-phase full-bridge converter for the AC/DC conversion and need separate DC–DC boost converter to increase the DC voltage. Compared to the conventional method, the proposed WPS uses three-phase/three-switch Vienna rectifier for AC/DC conversion and boosts the DC voltage. The boosted DC voltage is again boosted by ZSI to reduce the voltage sag and increase the quality of power of the off-grid system. The ZSI uses the shoot-through states to improve the DC link voltage and decrease the electromagnetic interference noise. The combination of Vienna rectifier and ZSI provides best quality performance which improves the efficiency and reduces cost and total harmonic distortion. MATLAB/Simulink software was used to simulate the proposed system. The feasibility of the proposed system is validated by simulation and prototype experimental results.